RETRACTED: Building a STEAM Educational Environment for Preschoolers Based on Natural Materials - Tiep, Pham Quang (VNU Journal of Science: Education Research, 2025)
This study aims to design, develop, and evaluate the effectiveness of a STEAM (Science, Technology, Engineering, Arts, and Mathematics) integrated learning environment based on natural materials for preschool children. Employing an experimental research method with a control group, the study was conducted at eight preschools in both urban and rural areas, involving 320 children aged 4 - 5 over a period of 16 weeks. The STEAM learning environment included 12 integrated learning corners utilizing locally sourced natural materials, designed to align with Vietnamese cultural characteristics. The findings indicate that the natural-material-based STEAM environment had a significantly positive impact on children's exploratory skills, creative thinking, collaboration ability, and learning engagement, with comparable effectiveness across urban and rural settings. The study proposes the “STEAM-N” model and offers recommendations for effectively implementing this approach in Vietnamese early childhood education, contributing to pedagogical innovation oriented toward competence development.